The Effectivenes Implementation of Lima Model on Discharge Readiness Among Patient Post Primary Percutaneous Coronary Intervention - Linda Linda; Desi Mitra Budi Yanti; Rosi Setia Aska; Lina Yerni Parlina; Dedwitayanni Dedwitayanni; Dila Mutiara Sukma (Jurnal Ners, 2025)
The use of the Percutaneous Coronary Intervention method as a revascularization method is increasing rapidly. Short hospitalizations and rapid recovery lead to reduced patient and family understanding of risk factors and prevention efforts of recurrent attacks, which are challenges to patient adherence to medication and self-care. Discharge Planning is the process of preparing the patient for continuity of care until the patient feels ready to return home. This study aims to determine the effect of the LIMA model on the discharge readiness of post Primary Percutaneous Coronary Intervention (post-PPCI) patients. This research uses a quantitative approach with a quasi-experimental design. Research design with post test only non equivalent control group approach. The number of samples used was 60 people divided into 30 intervention groups and 30 control groups. Data analysis using the Mann Whitney test. The results of this study showed that there was a significant difference between the intervention group and the control group on the implementation of the LIMA model with p value =